Confronting the Collateral Consequences of a Criminal Conviction: A Special Challenge for Social Work With Offenders - VELMER S. BURTON, JR.; Colleen M. Fisher; Cheryl Lero Jonson; FRancis T. Cullen (Journal of Forensic Social Work, 2014)
Millions of former offenders—often members of racial ethnic minority or other disenfranchised groups—experience restrictionson their legal and civil rights as the collateral consequences of their criminal conviction. It is critical for the social workers and other human service professionals who frequently interface with this population to understand these collateral consequences to effectively serve their clients with criminal convictions. This exploratory study examined the impact these collateral consequences may haveon social work practice with offenders. We assessed practitioners’ awareness, knowledge, and experiences with the collateral consequences of clients’ criminal convictions and practitioner efforts as‘‘agents of restoration’’ to pursue statutorily available court-ordered expungements of their clients’ criminal conviction records. Findings revealed that practitioners lacked awareness of collateral consequences, their application, and expungement. Recommendations to enhance social work practitioners’ ability to address andreduce the far-reaching collateral consequences of incurring acriminal conviction are discussed.